Beyond the Iron Triangle: improving the quality of teaching and learning at scale. Issue 7 (3rd July 2021) - Ryan, Tracii; French, Sarah; Kennedy, Gregor
ABSTRACT: Massification is a reality facing universities around the world. While increased access to higher education has significant social and economic benefits, rapid growth in class sizes challenges institutions to maintain quality standards while teaching at scale, amidst ongoing cost pressure. This paper analyses this issue within the Australian higher education context. It employs the notion of the 'Iron Triangle' to examine the tensions between what appear to be mutually conflicting concepts of access, cost and quality. It also highlights key strategies that can be employed to potentially enhance quality without dramatically inflating costs.